Does the sick physician have an accurate picture of his own disease? a bioethical dilemma - Battellini, Roberto (Revista del Hospital Italiano de Buenos Aires, 2020)
What is reported here is an experience lived in the convalescence of a disease by a cardiac surgeon within a hospital of closed clientele, at a time when there were no other services in the city and having been himself the “founder” of that same service, having to practice coronary revascularization. Illness definitely constitutes a new dimension of sensitivity, sometimes lacking in reasoning according to Broeckman2, or as Lolas Strepke says “the theorization on the role of being sick fails”, and that is what makes physicians end up in a labyrinth. So finally, we ask ourselves, who deals with the “care of the doctor” or the “care of the caregiver”? It is concluded that generally the doctor, being sick, has no realistic image of his own illness. We lack an analysis of the psychological narcissistic aspects of surgeons.